2019
DOI: 10.1055/s-0039-1697587
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Maternal Race and Ethnicity and Risk Factors for Primary Cesarean Delivery in Nulliparous Women

Abstract: Objective To understand whether maternal, perinatal, and systems-level factors can be identified to explain racial/ethnic disparities in cesarean delivery rates. Study Design This retrospective cohort study included nulliparous women with singleton gestations who delivered at a tertiary care center from 2015 to 2017. Maternal, perinatal, and systems-level factors were compared by race/ethnicity. Multilevel multivariable logistic regression was used to identify whether race/ethnicity was independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Black women with an NTSV pregnancy in this sample had an increased odds of having a cesarean compared with white women, even when adjusting for the other variables in the model. This increased odds of cesarean birth among Black women has been reported in many other studies that have controlled for maternal, perinatal, and system risk factors 6,36‐38 . Black women are also more likely to receive a cesarean for having Category II/III fetal heart rate patterns, whereas white women are more likely to have a cesarean for failure to progress 6,37 …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Black women with an NTSV pregnancy in this sample had an increased odds of having a cesarean compared with white women, even when adjusting for the other variables in the model. This increased odds of cesarean birth among Black women has been reported in many other studies that have controlled for maternal, perinatal, and system risk factors 6,36‐38 . Black women are also more likely to receive a cesarean for having Category II/III fetal heart rate patterns, whereas white women are more likely to have a cesarean for failure to progress 6,37 …”
Section: Discussionsupporting
confidence: 62%
“…This increased odds of cesarean birth among Black women has been reported in many other studies that have controlled for maternal, perinatal, and system risk factors. 6,[36][37][38] Black women are also more likely to receive a cesarean for having Category II/III fetal heart rate patterns, whereas white women are more likely to have a cesarean for failure to progress. 6,37 One clinical implication of the finding that higher doses of oxytocin are associated with a higher odds of cesarean might be to find ways to decrease oxytocin total dose exposure by discontinuing oxytocin for women in active labor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies also found gestational age of induced labor and induction methods were related to the incidence of cesarean [24,25]. The ethnic disparity was observed in cesarean delivery rates, Stark et al showed that the frequency of cesarean was lowest in non-Hispanic white women and highest in non-Hispanic black women [26]. In addition, delivery time, clinicians' personal beliefs and pregnant women themselves' views of decision-making also have an impact on delivery mode [27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…Past studies also found gestational age of induced labor and induction methods were related to the incidence of cesarean [27,28]. The ethnic disparity was observed in cesarean delivery rates, Stark et al showed that the frequency of cesarean was lowest in non-Hispanic white women and highest in non-Hispanic black women [29]. In addition, delivery time, clinicians' personal beliefs and pregnant women themselves' views of decision-making also have an impact on delivery mode [30][31][32].…”
Section: Discussionmentioning
confidence: 98%